ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PEMBELIAN RUMAH DI KOTA MADIUN - Yopie Diondy Kurniawan (J-MACC, 2021)
This study aims to analyze what factors influence the purchase of houses in the city of Madiun . The sample in this study amounted to 119 residents of the city of Madiun. The sampling technique in this study was conducted by insidential sampling method. The independent variables in this study are location, social environment, price, and community income while the dependent variable in this study is the purchase decision.The analysis in this study uses multiple linear regression which is done by testing classical assumptions first. The results showed that the price and environment had a positive and significant effect on the decision to buy a house in the city of Madiun, while the salary variable and location had a negative and insignificant effect on the purchase of a house in the city of Madiun.